2017
DOI: 10.1038/srep46242
|View full text |Cite
|
Sign up to set email alerts
|

apterous Brain Neurons Control Receptivity to Male Courtship in Drosophila Melanogaster Females

Abstract: Courtship behaviours allow animals to interact and display their qualities before committing to reproduction. In fly courtship, the female decides whether or not to mate and is thought to display receptivity by slowing down to accept the male. Very little is known on the neuronal brain circuitry controlling female receptivity. Here we use genetic manipulation and behavioural studies to identify a novel set of neurons in the brain that controls sexual receptivity in the female without triggering the postmating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…It has previously been reported that Apterous -GAL4 (Apt-GAL4) drives expression in the LHLK neurons, as well as neurons in the optic lobe and antennal mechanosensory and motor centers (AMMCs), and a small population of mushroom-body neurons (S2A Fig) [27,32]. Immunostaining with Lk antibody in Apt-GAL4>UAS-mCD8::GFP flies confirmed colocalization exclusively within the LHLK neurons (S2A and S2B Fig).…”
Section: Resultsmentioning
confidence: 78%
“…It has previously been reported that Apterous -GAL4 (Apt-GAL4) drives expression in the LHLK neurons, as well as neurons in the optic lobe and antennal mechanosensory and motor centers (AMMCs), and a small population of mushroom-body neurons (S2A Fig) [27,32]. Immunostaining with Lk antibody in Apt-GAL4>UAS-mCD8::GFP flies confirmed colocalization exclusively within the LHLK neurons (S2A and S2B Fig).…”
Section: Resultsmentioning
confidence: 78%
“…; Aranha et al. ), there is much potential to use this genetic model to gain access into the neuronal architecture of female control over paternity. Moreover, the propensity of D. melanogaster females to remate is not only influenced by food availability (Gorter et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that Apterous -GAL4 drives expression in the LHLK neurons, as well as neurons in the optic lobe, antennal mechanosensory and motor centers (AMMC), and a small population of mushroom body neurons (S2A Fig) [25,30]. Immunostaining with Lk antibody in Apterous -GAL4>UAS-CD8::GFP flies revealed co-localization exclusively localized to the LHLK neurons (S2A and S2B Fig).…”
Section: Resultsmentioning
confidence: 86%